Nuclear reaction cross sections and the optical potentials and for the n-12C and N-12C scattering - Moumene Imane; Bonaccorso Angela (EPJ Web of Conferences, 2024)
In this talk we first discuss total cross sections for the system n-12C in the incident energy range 20-500 MeV, calculated with a phenomenological optical potential and the optical model. We compare with calculations done with the eikonal model using the same potential and a single folding potential in the optical limit. Several single folding potentials are obtained using 12C densities from different models. These potentials are sensitive to the density used and none of them reproduces the characteristics of the phenomenological potential nor the cross section results. We then discuss nucleus-nucleus potentials and reaction cross sections for some projectiles on 12C within the eikonal formalism. We find that single folded projectile-target imaginary potentials and double folded potentials can produce similar energy dependence of the reaction cross sections but the single folding results agree better with experimental data provided the radius parameter of the phenomenological n-target potential is allowed to be energy dependent. We conclude that a single folding nucleusnucleus potential build on a phenomenological nucleon-nucleus potential can constitute an interesting and useful alternative to double folding potentials.